MANAJEMEN EMOSI SESUAI TUNTUTAN KERJA (EMOTIONAL LABOR) DITINJAU DARI TIPE KEPRIBADIAN PADA WIRANIAGA - Ratnaningsih, Ika Zenita (Jurnal Psikologi, 2015)
This study aims to investigate the difference in management of emotions as the demands of work (emotional labor) between extrovert and introvert salespeople. Subjects comprised 92 salespeople of the department store â€œXâ€ (82 women; 10 men), aged 18-40 years (mean of age 22 years). In average, subjects had finished high school/equivalent. The average tenure is 2.5 years. Data were collected using two scales: Eysenck Personality Questionnaire/EPQ (22-items; Î± = .865) and Emotional Labor Scale (11-items; Î± = .787). The results of t-testÂ showed that introvert salespeople scored significantly higher than the extrovert salespeople (Mintrovert = 36.08;Mextrovert = 33.67; t = 3.50; p = .001). It can be concluded that the introvert salespeople have better emotional labor than the extrovert salespeople.